(untitled) (International Journal of Physiotherapy, 2015)
Background: Even early in Eye disease, children have reduced economy of activity of daily living. Early eye examination, diagnosis and management will reduce the consequences of other system originated by eye problems. The current literature is aimed to provide and explore the knowledge of Pediatric Physical Therapist about pediatric eye examination. This will help in early detection of any eye disorder and in good prognosis of visual health, physical growth, social and mental health as well. Methods: The data and contents of current literature have been explored from different webpages, books and by personnel experience in pediatric physical therapy and optometry. Results: In the beginning disclosure and immediate treatment of ocular diseases in children is necessary to prevent lifelong visual deterioration. Checkup of the eyes should be carrying out early in the neonates period and at all well-child visits. Neonates should be checked for ocular structural abnormalities, such as cataract, corneal opacity, and ptosis, which are known to cause in visual problems. Every child who are bring into being have an ocular anomaly or who fail vision examination should be referred to a pediatric ophthalmologist or an eye care specialist appropriately trained to treat pediatric patients. Conclusions: Children account for a large and growing percentage of the population of the India. Studies have demonstrated that the prevalence of eye and vision disorders is substantial in this group. Researches also reveal that early detection and intervention are particularly important in children because of the very quick development of the visual system in early childhood and its sensitivity to interference. When disorders such as amblyopia and squint are undetected, the long-term consequences can be serious in terms of quality of life, comfort, appearance, and career opportunities.